Implementasi Double Frequency Modulation dan FFT dalam Sintesis Suara Rindik (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
The modern era has changed a lot of people's lives, for example traditional culture is slowly being abandoned which is being replaced by the ease of technology which is growing to affect people's lifestyles. One of them is gamelan culture in the Bali area, namely gamelan rindik. In the past, the rindik gamelan was usually used as an entertainment musical instrument played by village farmers, then for the joged roof performance and later adapted as a welcome musical instrument in hotels. However, along with the development of technology, making this gamelan less desirable because people, especially the younger generation, are more interested in modern musical instruments which are more attractive than traditional gamelan such as the rindik. Because of this, the author is interested in making a digital form of gamelan rindik by synthesizing the sound of gamelan rindik and then presenting it through a media website that can be accessed on any platform. This can be an introduction to the younger generation about gamelan rindik with a more attractive visual. Synthesizing requires a sound processing technique with a certain method commonly used, namely Double Frequency Modulation. However, before doing the synthesis, another method is needed to obtain the features that will be used during the synthesis, one of which is the frequency feature of the sound produced by the rindik gamelan. To get the frequency using the Fast Fourier Transform method. The research was conducted by analyzing 11 blades on the rindik and then the synthesis process was carried out. From the test results, it was found that the method used was successful in synthesizing using three datasets with each accuracy for dataset 1 having an accuracy of 36%, for dataset 2 having an accuracy of 100% and dataset 3 having an accuracy of 45%. This result was obtained by recording the sound of the rindik gamelan on its 11 blades